RISK MANAGEMENT IN UK CORPORATIONS: COMPARING FINANCIAL SERVICE INDUSTRY, OIL AND GAS INDUSTRY AND OTHER NON-FINANACIAL INDUSTRIES - Olaseinde, Olumide, K. (2012)
Abstract The focus of this research is to determine whether UK corporations (comparing firms in the financial service industry, oil and gas industry and other non-financial industries) have a more formal developed risk management process. Despite regulations and recommendations (such as the Walker review (2009), the Turner review (2009), the Financial Reporting Council (2011) etc.) there are only limited information on how firms manage risk and how they report risk management processes to their shareholders. This dissertation investigates in more detail how risk management varies between different industries, and aims to understand how firms manage and report on risk they face. In addition, the dissertation looks to ascertain whether large firms have a more formal developed risk management process than small firms and to understand whether industry sector affects risk management practice. This research produced a number of key findings: it showed that financial service firms have a more formal developed risk management process than other non-financial firms which was consistent with the research hypothesis; surprisingly oil and gas firms do not have a more formal risk management process than other non-financial firms, which was not consistent with the research hypothesis; and large firms have a more formal risk management process than small firms. The results are consistent with suggestion that financial service firms, due to their business, operations and importance to the economy, have an improved formal risk management process; also that firms implement risk management processes that best suit the circumstances and environment in which they operate. This research argues that there is a case for improved risk management practice across UK corporations: this is especially the case for oil and gas firms and other non-financial firms.